In other words, the sum of all the fractions of \(\zeta \left( n \right) \) from \(n=2\) to infinity is exactly 1. With a bit of handwaving here, it can be surmised that the sum of \(n\) Zeta functions starting at \(n=2\) is \(n-1+a\), where \(0<a<\). Hence the floor value is \(n-1\).

This proof-toid is incomplete because we need to prove additional lemmas, such as \(\zeta \left( n \right) >\zeta \left( n+1 \right) >1\) for all \(n\). But this is the gist of the proof anyway.

Indeed,
\[\sum_{k = 2}^\infty (\zeta(k) - 1) = 1\]
is the key identity. The rest of the proof is quite simple.

Each term \(\zeta(k) - 1\) is positive. It follows that
\[0 < \sum_{k = 2}^n (\zeta(k) - 1) < 1.\]
Then
\[n - 1 < \sum_{k = 2}^n \zeta(k) < n,\]
as desired.

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestFirst, observe that

\(\displaystyle\sum _{ k=2 }^{ \infty }{ \left( \zeta \left( k \right) -1 \right) } =\displaystyle\sum _{ k=2 }^{ \infty }{ \left( \displaystyle\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { n }^{ k } } } -1 \right) } =\displaystyle\sum _{ n=2 }^{ \infty }{ \sum _{ k=2 }^{ \infty }{ \frac { 1 }{ { n }^{ k } } } } =1\)

In other words, the sum of all the fractions of \(\zeta \left( n \right) \) from \(n=2\) to infinity is exactly 1. With a bit of handwaving here, it can be surmised that the sum of \(n\) Zeta functions starting at \(n=2\) is \(n-1+a\), where \(0<a<\). Hence the floor value is \(n-1\).

This proof-toid is incomplete because we need to prove additional lemmas, such as \(\zeta \left( n \right) >\zeta \left( n+1 \right) >1\) for all \(n\). But this is the gist of the proof anyway.

Log in to reply

Indeed, \[\sum_{k = 2}^\infty (\zeta(k) - 1) = 1\] is the key identity. The rest of the proof is quite simple.

Each term \(\zeta(k) - 1\) is positive. It follows that \[0 < \sum_{k = 2}^n (\zeta(k) - 1) < 1.\] Then \[n - 1 < \sum_{k = 2}^n \zeta(k) < n,\] as desired.

Log in to reply

Very nice!

Log in to reply

Interesting method. I tried squeezing it however I am having trouble establishing a good integer upper bound.

Log in to reply